MENINGKATKAN KETERAMPILAN KONSELING SEBAYA DENGAN MIND SKILLS - Muhammad Husni (PEDAGOGIK : JURNAL PENDIDIKAN, 2017)
Counseling is one of the counseling services, which serves to help the counselee gain understanding and clarify his views, to be used throughout his life, so he can make choices that are desirable and useful. Peer counseling skills, can occur when counselors are able to use counseling techniques and communication as well as mind-managing skills, called mind skills, which can be trained with experiential learning. This paper attempts to provide arguments and theoretical foundations about; the importance of peer counseling and counseling in Isalam, in enhancing peer counseling skills with mind skills in each counseling, since empirical studies have found that there are some counselors who can not provide comprehensive counseling services. Counselors in the field tend to be trapped with their own thoughts, so often overwhelmed by negative self-talk, and more play the role of a more experienced man, and then move his experience to the counselee